Desenvolvimento de um modelo numérico para avaliação do tempo em suspensão de partículas de aerossol em uma sala de aula - Batista, Heitor Luigi (Universidade Federal Rural do Semi-Árido, 2020)
Covid-19 is a highly contagious disease caused by the Sars-CoV-2 virus. Among the ways of virus spreading and possible contagion, the aerosol originated by the phenomenon of coughing or sneezing of an infected person stands out. As experimental studies are limited, considering the high contagiousness of the disease, numerical modeling of the aerosol flow problem is one of the best alternatives for studying this phenomenon. Based on this, the present work proposes a numerical approach to study the behavior of aerosol particles expelled by people in a classroom environment, where factors such as ventilation, temperature, proximity between people, objects and geometry of the environment directly influence the propagation and deposition of the particulate. The model was developed following an Euler-Lagrange approach in commercial software Ansys Fluent to model a classroom enviroment with particle injection originated from coughing, sneeze or talking events. With the obtainend results, it is possible to observe and analyze the behavior of the aerosol expelled in the classroom, such as maximum distance covered, length of suspension in the air and influence of the air flow in the classroom and thus obtain behavioral parameters of the expelled particles, which can be of great help in terms of preventing the virus spreading in a closed environment.
Keywords: Covid-19; Aerossol; Euler-Lagrange; ENGENHARIAS::ENGENHARIA MECANICA